(untitled) (Revista de Artes Marciales Asiáticas, 2023)
Objective. To measure rapid weight loss and urinary indicators of hydration status, as well as to assess the effects and symptoms of dehydration in Brazilian jiu-jitsu (BJJ) athletes at different moments. Methods. 17 male BJJ athletes (aged: 24.4 ± 3.5 years; body mass (BM): 76.8 ± 14.6 kg; body fat: 16.6 ± 6.4%), were evaluated between 8 and 9 am at three different moments: Baseline (10 days pre- competition), measurement of BM and stature, collection of urine samples, and food record of the previous 24 hours; pre-competition, measurement of BM, urine samples, and questionnaire to assess rapid weight loss (RWL), and post-competition (24h after), day after competition, with measurement of BM, and urine samples for analysis of specific gravity. Results. There was a tendency to decrease BM to compete (baseline: 76.8 ± 14.6 kg, pre-competition: 75.4 ± 13.4 kg, post-competition: 77.3 ± 13.7 kg; p < 0.07), with 88.2% of athletes using methods that increase dehydration. The majority of athletes were dehydrated at the three time points of the study (94.1%; USG = 1.021 ± 0.005 Usg at baseline, 88.2%; 1.020 ± 0.007 Usg at pre-competition, 88.2%; 1.022 ± 0.008 Usg on the post-competition day), accompanied by symptoms associated with RWL (82.4% increased heart rate, 52.9% headache, 47.1% hot flashes, 41.2% nausea, 41.2% disorientation, and 29.4% dizziness). Conclusions. Rapid pre-competitive weight loss and symptoms associated with dehydration were observed in the BJJ athletes. It is recommended that educational measures are promoted to inhibit RWL among BJJ athletes, requiring the engagement of health professionals and organizations that govern the sport (federations and confederations).